Prospective evaluation of RASSF1A cell-free DNA as a biomarker of pre-eclampsia. Issue 9 (September 2015) - Salvianti, Francesca; Inversetti, Annalisa; Smid, Maddalena; Valsecchi, Luca; Candiani, Massimo; Pazzagli, Mario; Cremonesi, Laura; Ferrari, Maurizio; Pinzani, Pamela; Galbiati, Silvia
Abstract Introduction This study aims to quantify total and fetal cell-free DNA (cfDNA) in maternal plasma at different gestational ages and to assess whether this could represent a reliable predictive marker of pre-eclampsia (PE) before clinical onset. Methods We performed a qPCR assay to compare the cfDNA concentration of hypermethylated and unmethylated RASSF1A promoter gene sequences in maternal plasma among 3 groups of pregnant women. These included 17 women with overt PE, 33 women at risk for the disease subsequently differentiated into 9 who developed PE and 24 who did not, and 73 controls. All women at risk were consecutively sampled throughout the whole gestation. Results Both total and fetal cfDNA had a good diagnostic performance in distinguishing patients with overt PE from healthy controls. When comparing women at risk who developed PE to women at risk who did not, the predictive capability was satisfactory at a gestational age ranging from 17 to 30 weeks. This allowed establishing within this time interval a cut-off value of 735 GE/ml for total cfDNA (87.5% sensitivity and 70.0% specificity), and a cut-off value of 7.49 GE/ml for fetal cfDNA (100% sensitivity and 50% specificity). cfDNA levels turned positive several weeks before the onset of the disease: from 2 to 18 weeks for total cfDNA and from 8 to 17 weeks for fetal cfDNA. Discussion The simultaneous use of total and fetal cfDNA would allow an accurate monitoring and prevention of PE development thus suggesting that RASSF1A could represent a potential biomarker of PE.